The dose-effect relationship of acupuncture on limb dysfunction after acute stroke: a systematic review and meta-analysis - Wang, Xiaoxuan; Xiao, Lu; Xiao, Lingyong; Tian, Chunlei; Liu, Yi; Dai, Xiaoyu (Frontiers in Neurology, 2024)
This study aimed to investigate the relationship between the dose and efficacy of acupuncture in treating limb dysfunction during acute stroke. Methods: Studies were searched from seven databases, including PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, Wanfang Data, VIP information database , and China Biology Medicine Database. All databases were searched until August 1, 2023 from inception. The risk of bias was assessed using Cochrane Collaboration's risk of bias tool. The primary outcome measure by FMA. We performed a meta-analysis using a 3-step process. First, we investigated the dose-related effects of acupuncture at varying doses and determined the optimal dosage for maximum therapeutic benefits. Second, we determined the difference between post-intervention and baseline scores on the outcomes of interest to determine MCID to provide evidence for clinical treatment. Third, by combining the results of step 1 and step 2, we made the recommendations employing the Grades of Recommendations, Assessment, Development and Evaluations tool.Results: 26 studies containing 1947 participants were included, among which 61.5% of RCTs had a low risk of bias. Regarding the frequency of acupuncture, the results demonstrated a significant improvement in the low and moderate-frequency groups (low frequency: MD: 9.02, 95%CI: 5.40 to 12.64, p<0.00001; moderate frequency: MD: 10.11, 95%CI: 5.05 to 15.18, p<0.00001, I 2 =0%). For the acupuncture retention time, the results showed no significant difference between the short and medium retention groups (short retention time: MD: 0.05 ,95% CI: -0.21 to 0.31, p=0.71; medium retention time: MD: -1.16 ,95% CI:-2.80 to 0.48, p=0.17, I 2 = 99%). For the course of acupuncture, the results showed a significant improvement in the short course group (MD: 14.87, 95% CI: 12.18 to 17.56, p<0.00001, I 2 = 0%).Our study demonstrated the effectiveness of different acupuncture dose in improving limb dysfunction. The pooled data suggested that the optimal intervention dose for acupuncture interval time was low and moderate frequency, the optimal intervention dose for needle course time was short course treatment . But we did not find the optimal intervention dose for needle retention time. Future studies of higher quality are needed to confirm this.